Viruses in Simuliidae: An Updated Systematic Review of Arboviral Diversity and Vector Potential - Rivera-Martínez, Alejandra; Rodríguez-Alarcón, Carlos Arturo; Garza Hernandez, Javier Alfonso; Laredo-Tiscareño, S. Viridiana; Adame-Gallegos, Jaime R.; de Luna-Santillana, Erick de Jesús; García-Rejón, Julián E.; Casas-Martínez, Mauricio (2025)
Black flies (Diptera: Simuliidae) are important vectors of pathogens, including filarial nematodes, protozoans, and arboviruses, which significantly impact human and animal health. Although their role in arbovirus transmission has not been as thoroughly studied as that of mosquitoes and ticks, advances in molecular tools, particularly metagenomics, have enabled the identification of non-cultivable viruses, significantly enhancing our understanding of black-fly-borne viral diversity and their public and veterinary health implications. However, these methods can also detect insect-specific viruses (i.e., viruses that are unable to replicate in vertebrate hosts), which may lead to the incorrect classification of black flies as potential vectors. This underscores the need for further research into their ecological and epidemiological roles. This systematic review, conducted following the PRISMA protocol, compiled and analyzed evidence on arbovirus detection in Simuliidae from scientific databases. Several arboviruses were identified in these insects, including vesicular stomatitis virus New Jersey serotype (VSVNJ), Venezuelan equine encephalitis virus (VEEV), and Rift Valley fever virus. Additionally, in vitro studies evaluating the vector competence of Simuliidae for arboviruses such as dengue virus, Murray Valley encephalitis virus, and Sindbis virus were reviewed. These findings provide critical insights into the potential role of black flies in arbovirus transmission cycles, emphasizing their importance as vectors in both public and veterinary health contexts.